Synthesis of Uronic Acid Building Blocks and Their Application in Oligosaccharide Synthesis - Tiwari, Varsha (IIT(BHU) Varanasi, 2022)
Abstract is available in the attachment
Keywords: Synthesis of Uronic Acid; Oligosaccharide; Synthesis; Building Blocks